The Sedimentary Facies and Evolution Characteristics of the Middle and Deep Strata in the Nanpu No. 3 Structural Area - Zhang, Hui; Lan, Zhiqin; Li, Xiaoyan; Huang, Xinglong (Frontiers in Earth Science, 2021)
In this study, due to the inconsistencies in the understanding of the sedimentary types in the second section of the Dongying Formation (Ed2) and the third section of the Shahejie Formation (Es3) in the middle and deep strata of Nanpu No. 3 structural area, the depositional characteristics of the deep braided river delta, fan delta, deep-water slump turbidite fan, and coastal and shallow lake in the Nanpu No. 3 structural area were examined in-depth. The investigations were begun based on the descriptions and observations of core samples obtained from eight cored wells in the study area, in combination with seismic, well logging, and rock ore data. The results revealed that the sources of the material in the study area originated from the Shaleitian salient in the southwest direction. It was determined that the fan deltas and the shallow lake sedimentary system had developed during the SQ1 sequence and SQ2 sequence periods. The braided river deltas and the shallow lake and turbidite sedimentary system with multi-stage superposition had developed during the SQ3 to SQ7 sequence periods, and their distribution range had been controlled by the structural background of the gentle slope zone of the lake basin. On that basis, a sequence deposition filling model controlled by a slope break zone in the middle and deep strata of the Nanpu No. 3 structural area was established in this study starting from the typical seismic profile, in which such factors as the tectonic activity characteristics, lake basin boundary shape, water depths, and so on, were comprehensively considered. The goal of this research investigation was to provide beneficial information for oil and gas explorations in similar areas.